Improving sustainability of inland Pacific Northwest dryland agriculture systems with pea-canola intercropping: a review - Stubbs, Lauren R.; Singh, Surendra; Wysocki, Donald; Heineck, Garett C.; Neely, Haly L.; Singh, Shikha (Frontiers in Sustainable Food Systems, 2025)
Changing weather conditions are having negative impacts on dryland (rainfed) crop production systems such as those found in the inland Pacific Northwest (iPNW). This region is dominated by winter wheat (Triticum aestivum L.) production and also produces alternative crops such as canola (Brassica napus L.) and peas (Pisum sativum L.). Producers need crop rotations and agronomic management strategies that are equally productive and more sustainable than traditional winter wheat-fallow systems. New crop rotations should prioritize crop water use efficiency (WUE), protect soil health, and manage herbicide-resistant weeds. Intercropping is one practice that can promote agroecosystem biodiversity, soil health, drought resilience, and resource use efficiency (RUE), among other ecosystem services. Spring pea and spring canola intercropping, also referred to as “peaola,” is emerging as an alternative crop rotation and management strategy for the dryland iPNW mainly because it increases RUE and WUE, while reducing production inputs. However, little is known about producing peaola in the iPNW. Therefore, this review seeks to address a wide range of topics, including (but not limited to) ecological and agronomic aspects of intercropped systems, the impact of peaola production on soil health, the potential of peaola to reduce pest pressure and improve drought resilience, and examples of barriers that may prevent the adoption of peaola in the iPNW. Findings indicate that peaola can provide agroecosystem benefits such as improved water infiltration, soil organic matter turnover, nutrient cycling, and increased land use efficiency. However, complexity of management, a lack of region-specific research, and marketing constraints are legitimate challenges barring the immediate adoption of peaola. Nonetheless, peaola has the potential to improve cereal crop production and promote sustainability in dryland agricultural systems across the iPNW.